Use the Internet and Facebook in ecuadorian teenagers [Uso de Internet y la Plataforma Facebook en Adolescentes Ecuatorianos] - Yaguache Quichimbo, J. (2016)
This research includes the study of Internet use and the social network Facebook in adolescents of Ecuador 2015. We worked with a sample of 30 educational level institutions in 13 cities of Ecuador, were performed 7542 surveys in the population under study were adolescents tenth year of basic education to the third year of high school (14-18 years), considered generationally as Millennials. The results indicate that the main uses of the Internet in this specific group include watching videos on Youtube and social networks-specifically enter Facebook-where the most important activities and times when accessing these users, now known as prosumers are verified. © 2016 AISTI.